2012
DOI: 10.1002/pro.2175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental support for the foldability–function tradeoff hypothesis: Segregation of the folding nucleus and functional regions in fibroblast growth factor‐1

Abstract: The acquisition of function is often associated with destabilizing mutations, giving rise to the stability-function tradeoff hypothesis. To test whether function is also accommodated at the expense of foldability, fibroblast growth factor-1 (FGF-1) was subjected to a comprehensive u-value analysis at each of the 11 turn regions. FGF-1, a b-trefoil fold, represents an excellent model system with which to evaluate the influence of function on foldability: because of its threefold symmetric structure, analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 68 publications
(85 reference statements)
4
55
0
Order By: Relevance
“…In preceding studies, residues in β-strand 2 and β-strands 5-8 are protected in the early stage of folding revealed by H/D exchange experiments of NMR [17,18]. Longo et al [13][14] and Xia et al [15] reported that the folding nucleus detected by the ϕ-value analyses consists of residues 16-58 in β-strands 2-6. Figures 3 and 4 presents the ADM and the F-value plot with the results of the H/D exchange experiment for 2K8R.…”
Section: Adm and F-value Analyses For β-Trefoil Proteins Of Which Folmentioning
confidence: 97%
See 4 more Smart Citations
“…In preceding studies, residues in β-strand 2 and β-strands 5-8 are protected in the early stage of folding revealed by H/D exchange experiments of NMR [17,18]. Longo et al [13][14] and Xia et al [15] reported that the folding nucleus detected by the ϕ-value analyses consists of residues 16-58 in β-strands 2-6. Figures 3 and 4 presents the ADM and the F-value plot with the results of the H/D exchange experiment for 2K8R.…”
Section: Adm and F-value Analyses For β-Trefoil Proteins Of Which Folmentioning
confidence: 97%
“…simulations [20,21] for FGF-1, IL-1β and for His were performed to identify their folding mechanisms. These studies revealed the differences in overall folding pathways among these proteins, while these proteins commonly start to fold at the central β-strands [13,17].…”
Section: Analyses With Inter-residue Average Distance Statistics Conmentioning
confidence: 99%
See 3 more Smart Citations